(untitled) (Research, Society and Development, 2020)
The Public Education is one of the main abilities on the State Administration, and that’s why, the big responsibility is attributed to the school management, in which the capacity is considered by studious of the area as fundamental condition to the implementation and leading the educational politics. As a consequence, this study set as a goal analyze the capacity received by managers of the public schools that offer the primary education located in Teófilo Otoni./MG. It’s about a descriptive study, of qualitative kind, developed by bibliographic meanings, documental and on camp. The data collected were processed using the content analyze. It was noticed that the initial academic formation of the managers interviewed didn’t contributed so much for their acting as managers, and the empiric capacity was elected as a support for the management exercise. However, even added, both isn’t enough to prepare them to the diary challenges of school management. Five of the seven managers interviewed participated of the Distance Training Program for School Managers (Progestão) that revealed outdated and minus useful on the school’s managerial demands. Besides this, didn’t had participation of the managers in any other institutional program of capacity, what impose in the decisions took at daily lived experience on the academic routine.